Prevalence of Symptomatic Heart Failure with Reduced and with Normal Ejection Fraction in an Elderly General Population–The CARLA Study - Tiller, Daniel; Russ, Martin; Greiser, Karin Halina; Nuding, Sebastian; Ebelt, Henning; Kluttig, Alexander; Kors, Jan A.; Thiery, Joachim; Bruegel, Mathias; Haerting, Johannes; Werdan, Karl (PloS one, 2013)
Chronic heart failure (CHF) is one of the most important public health concerns in the industrialized world having increasing incidence and prevalence. Although there are several studies describing the prevalence of heart failure with reduced ejection fraction (HFREF) and heart failure with normal ejection fraction (HFNEF) in selected populations, there are few data regarding the prevalence and the determinants of symptomatic heart failure in the general population. Cross-sectional data of a population-based German sample (1,779 subjects aged 45-83 years) were analyzed to determine the prevalence and determinants of chronic SHF and HFNEF defined according to the European Society of Cardiology using symptoms, echocardiography and serum NT-proBNP. Prevalence was age-standardized to the German population as of December 31st, 2005. The overall age-standardized prevalence of symptomatic CHF was 7.7% (95%CI 6.0-9.8) for men and 9.0% (95%CI 7.0-11.5) for women. The prevalence of CHF strongly increased with age from 3.0% among 45-54- year-old subjects to 22.0% among 75-83- year-old subjects. Symptomatic HFREF could be shown in 48% (n = 78), symptomatic HFNEF in 52% (n = 85) of subjects with CHF. The age-standardized prevalence of HFREF was 3.8 % (95%CI 2.4-5.8) for women and 4.6 % (95%CI 3.6-6.3) for men. The age-standardized prevalence of HFNEF for women and men was 5.1 % (95%CI 3.8-7.0) and 3.0 % (95%CI 2.1-4.5), respectively. Persons with CHF were more likely to have hypertension (PR = 3.4; 95%CI 1.6-7.3) or to have had a previous myocardial infarction (PR = 2.5, 95%CI 1.8-3.5). The prevalence of symptomatic CHF appears high in this population compared with other studies. While more women were affected by HFNEF than men, more male subjects suffered from HFREF. The high prevalence of symptomatic CHF seems likely to be mainly due to the high prevalence of cardiovascular risk factors in this population.